TOWARDS A DESIGN OBSERVATORY: THE CASE OF SCHOLARLY DESIGN RESEARCH IN PORTUGAL. (May 2020) - Costa, N.; Branco, V.; Costa, R.; Borges, A.; Modesto, A.; Silva, C.; Cunca, R.
Abstract: The DesignOBS project was created to collect, map and interpret data about the Portuguese Design Ecosystem, providing supportive information for decision making. This study takes advantage of a participative Design perspective to define and test an observation process via a case based on Design doctorates undertaken in Portugal. It emphasises the need for additional participatory analysis and curation by experts to evaluate and develop more reliable information about the discipline. Moreover, it develops recommendations that can enhance the communicability of Design doctorates.